Comparison of Spatiotemporal Gait Variables Between Healthy Individuals and Patients with Heel Spur During Walking - Mohamad amin Shahbazi; Ali Jalalvand (Biyumikānīk-i varzishī)
Objective This study aimed to investigate the differences in spatiotemporal gait parameters between healthy individuals and patients with plantar fasciitis, commonly referred to as heel spurs. Plantar fasciitis is a common foot condition that affects gait mechanics due to pain and inflammation in the plantar fascia. Understanding these differences can provide insights into how this pathology alters gait and inform therapeutic interventions to improve function and reduce discomfort. Methods The study population comprised two groups: patients diagnosed with plantar fasciitis and healthy controls. A total of 30 male participants aged 30–49 years were selected through convenience sampling, divided into two groups of 15 each. Inclusion criteria for the patient group included a confirmed diagnosis of plantar fasciitis and a minimum pain score of 3 on the numeric-visual scale. Exclusion criteria included the presence of other musculoskeletal, neurological, or systemic disorders. Spatiotemporal gait parameters were recorded using Vicon high-speed cameras at a sampling frequency of 100 Hz during walking trials. Data were tested for normality using the Shapiro-Wilk test, and statistical differences between groups were analyzed using the independent t-test in SPSS software, with a significance level set at p ≤ 0.05. Results Individuals with plantar fasciitis exhibited a higher percentage of double support, step time, stride time, and visual pain intensity, alongside lower cadence and walking speed compared to the healthy control group. Conclusion Time-related spatiotemporal gait parameters in patients with plantar fasciitis appear to be more sensitive to pathology, with increases in time-related variables and decreases in cadence and walking speed. However, certain spatiotemporal gait parameters (e.g., ipsilateral and contralateral foot-off) seem less affected